Economic Analysis : Application of Technology in Law Enforcement in Combating Corruption - Sarbini; Rakha Afkary; Hafidah Zalma's Love Aura (PT FORMOSA CENDEKIA GLOBAL, 2023)
The massive corruption cases that occur in Indonesia prove that there is a need for effective and efficient law enforcement efforts to eradicate corruption cases that occur, in handling it is necessary to apply technology to streamline the course of law enforcement, law enforcement efforts to eradicate corruption are regulated in Law No. 19 of 2019 concerning the second amendment to Law No. 30 of 2002 concerning the Corruption Eradication Commission. The problems that will be discussed in this study are related to economic analysis and the application of technology in law enforcement and corruption eradication. The research method used in this study is a normative research method using a legislative approach and a case approach and will be analyzed using content analysis.